EFEKTIFITAS PENGOLAHAN AIR EFFLUENT MENJADI AIR REKLAMASI DI INSTALASI PENGOLAHAN AIR LIMBAH SUWUNG DENPASAR DITINJAU DARI KANDUNGAN KEKERUHAN, TOTAL ZAT TERLARUT (TDS), DAN TOTAL ZAT TERSUSPENSI (TSS) - Widya Kalfika Devi, Luh Putu; Dharma Putra, K. G.; Bawa Putra, A. A. (Jurnal Kimia (Journal of Chemistry); Vol. 7, No. 1 Januari 2013, 2013)
The application of water reclamation system has been researched for the concentrations of Total Suspended Solid (TSS), Total Dissolved Solid (TDS), and turbidity in the effluent of waste water treatment in Suwung Denpasar. The aims of the research are to determine the effect of each stage of water reclamation, to determine the effectiveness water reclamation system and to know the quality reclaimed water. The results showed that each stage of water reclamation system can decrease the concentrations of TSS, TDS, and turbidity from effluent. The percentage of reduction of TSS, TDS, and turbidity  in biological filtration system were  85.60 %, 63.75 %, and 62.78 % respectively. The pre-ozonation system were 63.82 %, 64.93 %, and 73.78 % respectively and the coagulation and membrane systems were 60.58 %, 92.48 %, dan 74.58 % respectively. The overall rate of effectivenes of waste water reclamation system was 97.94% for TSS, 99.04% for TDS and 97.52% for turbidity.
Keywords: reclamation system, effectiveness, effluent, reclaimed water, the quality